Laparoscopic Repair of Right Paraduodenal Hernia in Adult Patients: Case Report and Literature Review - Tomoko Takagishi; Yuta Niimi; Goshi Matsuki; Shinta Nagano; Junsuke Hinami; Masaaki Kajiwara; Kiyoshi Kaneko; Yoshihiro Kubota; Osamu Nakai (Case Reports in Surgery)
A 56-year-old Japanese female presented with vomiting, nausea, and abdominal pain after excessive drinking and eating. Abdominal computed tomography showed an encapsulated circumscribed cluster of jejunal loops in the right upper quadrant. She was diagnosed with a strangulated intestinal obstruction caused by right paraduodenal hernia (PDH) and underwent an emergency laparoscopic repair. A view through the endoscope showed the right PDH, which was encapsulated under the mesocolon. Most of the small bowel was entrapped and adhered inside the sac, requiring careful adhesiolysis. The hernia orifice was expanded to a sufficient degree, and the strangulation was relieved, avoiding the need of resecting the small intestine. Recovery was uneventful, and the patient remains free of symptoms 3 years after surgery. Findings in a total of 29 patients (including this report) who underwent laparoscopic repair of right or left PDHs in Japan are discussed.